The concept of resilience- the scientific adaptation for society health - Svence, Guna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The main idea of the paper to indicate the factors of resilience indicators. The task of the research - a theoretical analysis of the latest research resilience factors and resilience risk factors and to analyze the theory of the intervention of positive psychology and development programs. Based on quantitative methods (narrative content analysis) recognise the contents of resilience and create the resilience factor model. Author together with students form RTTEMA master study programme “Psychology” during last 4 years (Svence and Nereta, Pumpurina, Stale, Berzina, 2009-2012) has created a positive intervention author programme “Resilience skills training” and adapted in Latvian term “resilience” together with scale of resilience (Resilience Scale, RS, Wagnild & Young, 1993). Eksperimental programmes was based on the Penn Resilience Programme (Seligman at al, 1999) and Masters Resilience Trainer (Gillham, Reivich, & Jaycox, 2008 Reivich & Seligman, 2008) programms which include the vitaly of skills development (self-regulation, hardiness, optimism, meaningful live, character strengths, etc). The practical aim is to analyse and compare resilience indicators in the groups of different ages (this article will analyse one of them- 40-50 years old wimin leaders group) in the period of twelve weeks by using experimental program of positive intervention. One of researches (Svence, Berzina, 2011-2012) participants narrative content analysis proves that individuals with daily stress caused by various stressors, and it significantly affects psychological wellbeing, as a result of these stressors can be added to the resilience risk factors because they increase human adaptive interference. Narrative content analysis proves that, for examples, women's resilience is the compilation of the resources - the vitality of the personality resources, which includes the force of will, hope, optimism, ability to adapt to change, stress tolerance, ability to solve problems and make decisions, positive thinking and attitude towards yourself and life in general . Women's are important resilience factors is social support of relatives, which gives strength and comfort, communicating with other, previous experience, understanding of the resources resilience, sense of responsibility, positive attitudes towards themselves, belief in yourself and the desire to improve themselves. After the intervention of quantitative analysis of the results of the study the author concludes that resilience is a set of skills that can be developed. It is proved by the results of the indicators before and after the intervention is received as well as by the results achieved in positive psychology (Seligman et al, 1999; Gillham, Reivich, & Jaycox, 2008 Reivich & Seligman, Jackson, & Watkins, 2004, Khoshaba , Maddi, 1999, Gillham et al. 1991; Reivich, Shatte & Gillham,2003). Authors has approbated the programm “Resilience skills training” and has approved Resilience scale (Resilience Scale, RS, Wagnild & Young, 1993, translated by G. Svence, I.Berzina, 2011) and created a resilience factor theoretical and experimental model.